Characterization and application of chondroitin sulfate/polyvinyl alcohol nanofibres prepared by electrospinning. (5th June 2016) - Guo, Junxia; Zhou, Huitong; Akram, Muhammad Yasir; Mu, Xueyan; Nie, Jun; Ma, Guiping
Highlights: Chondroitin sulfate/polyvinyl alcohol nanofibres was prepared by electrospinning. The nanofibres showed excellent cell compatibility in vitro. The drug-loaded nanofibres used as a model for testing drug release. Abstract: Composite nanofibres were prepared by electrospinning from a solution of chondroitin sulfate and polyvinyl alcohol. The chondroitin sulfate/polyvinyl alcohol (CS/PVA) mass ratios of 7/3 has a uniform and smooth morphology, and the average diameter of the nanofibres was 136 nm. Combretastatin A-4 phosphate was loaded on the nanofibres and used as a model for testing drug release from the nanofibres crosslinked with glutaric dialdehyde. The morphology and structure of the nanofibres was determined using scanning electron microscopy. In order to assess their possible application to tissue engineering scaffolds, the toxicity and cytocompatibility of the nanofibres were tested by methylthiazolydiphenyl-tetrazolium bromide assay.